PENGARUH R&D INVESTMENT DAN GROWTH OPPURTUNITY TERHADAP KINERJA KEUANGAN DAN ENVIRONMENTAL DISCLOSURE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTARDI BEI PERIODE 2017-2020 - Harahap Rulan Sari Kholidah; Rokhhmawati Andewi; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of r&d investment and growth opportunities on financial performance and environmental disclosure as intervening variables in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period and selected based on criteria so that 44 companies were obtained. Secondary data was collected using documentation techniques by collecting data on r&d investment, growth opportunities, financial performance and environmental disclosure during the research period in the annual report published on the IDX. The results of the study show that R&D Investment has a positive and significant effect on Environmental disclosure; Growth opportunity has a positive and significant effect on Environmental disclosure; R&D Investment has a negative but not significant effect on Financial Performance Growth opportunity has a negative but not significant effect on Financial Performance Environmental disclosure has a positive and significant effect on Financial Performance; R&D Investment has a positive and significant effect on Financial Performance with Intervening Environmental disclosure; Growth opportunity has a positive and significant effect on Financial Performance with Intervening Environmental Disclosure.Keywords: r&d investment, growth oppurtunity, firm peformance, environmental disclosure